Brooklyn nine-nine. Season two [videorecording (DVD)] - Samberg, Andy, 1978-; Braugher, Andre; Crews, Terry, 1968-; Fumero, Melissa, 1982-; Lo Truglio, Joe, 1970-; Peretti, Chelsea, 1978-; Beatriz, Stephanie (Universal Studios Home Entertainment, 2015)
Return to the scene of comedy so good, it's criminal. The second season episodes of the Golden Globe Award-winning Brooklyn Nine-Nine. Detective Jake Peralta and Captain Raymond Holt are back for more hilarious hijinks as they team up with Brooklyn's finest to make the precinct better than ever. As they deal with overbearing superiors, a drug task force, dating crimes, the questionable motives of close family, and a long-awaited interdepartmental romance.